Migraine Surgery A Clinical Guide to Theory and Practice - Muehlberger, Thomas (Springer International Publishing, 2018)
Migraine surgery is the only existing treatment option that can lead to a permanent symptomatic improvement. Surgical techniques and advances in the understanding of the underlying mechanisms are evolving rapidly. This book intends to familiarise surgeons with the concept of migraine headaches and explains the surgical deactivation of trigger sites, which consists of much more than the decompression of pericranial nerves. The traditional notion of the brain as the sole origin of migraine is supplanted by a concept where the alteration of afferent signals in conjunction with peripheral and central sensitization can trigger a migraine attack. Migraine surgery targets the crucial role of extracranial tissues in the genesis of migraine which is corroborated by substantial clinical, anatomical and pathophysiological evidence.